SCREENING METHOD OF THE DYSPLASIA OF THE CONNECTIVE TISSUE IN ADOLESCENTS - G. Y. Kalaeva; O. I. Khokhlova; I. A. Deev (Бюллетень сибирской медицины, 2016)
ABSTRACT Aim of the study is to develop the diagnostic checklist based on the incidence and significance analysis of the external features of the dysplasia of the connective tissue (DCT) for its screening and assessment of its prevalence in the adolescents’ population.Materials and methods.110 adolescents (aged from 10 to 14 years) were examined, 81 of them had the dysplasia of the connective tissue (the first group). The second group was presented by 29 adolescents without DCT. The presence and degree of manifestation of DCT were established according to the criterions of Kadurina T. I., Gorbunova V.N. (2009), Т. Milkovska–Dimitrova (1987). There were the physical, laboratory and instrumental examination. Statistical processing of the results was carried out using Statistica 6.0 program and IBM SPSS Statistics 20.0. The diagnostic efficiency of the developed checklist was appreciated by means of the receiver operating characteristic curve (ROC curve). Results. The frequent occurrence of the DCT’s external features in adolescents was identified. The diagnostic checklist was developed. It was consisted of 12 items with illustrations, allowing readily identification of the dysplastic phenotype presence with diagnostic sensitivity 81.5% and specificity 79.3%. This checklist can be recommended as for the population studies, as for screening about DCT in adolescents during the primary outpatient pediatrician attendance. In the positive result of the screening it is necessary the further checkup to detect the organ changes and diagnosis updating.